an Analytical Study of Imam Al-Ghazali’s Ayyuhal Walad Book: Implications for Contemporary Moral Education in Adolescents - arika amalia; Aisyah Ma'awiyah; Jufri (Yayasan Pendidikan dan Kemanusiaan Hurriah Aceh, 2025)
The complexities of moral teaching in modern society have intensified due to the rapid impact of globalization, technological progress, and evolving social dynamics. Concerns include moral degradation, reduced reverence for teachers and parents, and increasing misbehavior among adolescents demand immediate intervention from the educational system. This study employs a descriptive qualitative methodology through a library research approach. The principal source is Ayyuhal Walad by Imam Al-Ghazali. Data collection was executed using documentation, and content analysis was employed for data interpretation. The findings suggest that Imam Al-Ghazali’s insights in Ayyuhal Walad establish a significant basis for moral teaching among adolescents. His ideology emphasizes the necessity of a comprehensive equilibrium between academic advancement and emotional-spiritual growth, contending that knowledge devoid of virtuous behavior, genuine aim, and spiritual purification is ineffectual. Al-Ghazali's educational philosophy synthesizes intellect, emotion, and spirit, striving for ethical excellence and proximity to the holy. His ideas are significantly pertinent to contemporary moral education frameworks, providing a structure that promotes both academic proficiency and spiritual and ethical development. Al-Ghazali's educational framework—comprising tazkiyah, takhalli, and tahalli—constitutes an essential enhancement to contemporary education systems that frequently overlook moral and spiritual growth.